徐渭边防诗研究 = Study of Xu Wei's frontier poems - 刘昶 Liu, Chang (2013)
本文绪论部分首先明确了研究范围是徐渭的边防诗，边防诗又包含海防诗和塞防诗，本文对这三个称谓下了定义。笔者在《徐渭集》收录的 2200 余首诗歌中筛选出哪些是边防诗，还对从 2004-2012 年的徐渭诗歌研究论文进行了整理归纳。最后提出了几个文本分析基础上的深度发掘点。正文分为三章，为本文的重点，按时间顺序排列。第一章是诗人参与战斗时期作的海防诗，文本分析的代表作是《赠俞参将公》、《龛山凯歌九首》、《严氏女》。他的海防诗既有对战争场面的描写和对战争胜利的颂扬，也有对战争意义的反思和对建功立业的渴望。《严氏女》是徐渭海防诗同时也是女性诗题材的代表作，具有很高的研究价值。第二章是诗人在胡宗宪幕府时期作的海防诗，文本分析的代表作是《胡令公镇浙》和《凯歌一首赠参将戚公》，徐渭不再亲身参加战斗，只以胡宗宪幕僚的身份献计献策。他有时需要压抑自己的性格并放下身段奉承奸相严嵩一党，虽然内心深处有矛盾、惭愧的情绪，却并不后悔。他的人生态度总体来说仍然是积极向上的，他在这一时期所作的诗歌在思想上更有复杂性。本文还以徐渭的《凯歌一首赠参将戚公》与同时期另一位诗人沈明臣的《凯歌》进行对比研究。第三章是诗人在吴兑幕府时期作的塞防诗。文本分析的代表作是《胡市》和《西北三首》。他创作了数十首诗来反映边地的风貌和民族融合的局面，和平是主旋律。在此之前，徐渭已经经历了一生之中最大的困境，即被困在狱中七年并且失去了生员身份。这不仅代表他今后完全丧失了科举出仕的希望，更代表了他的身份变成了庶民，他因此非常痛苦。徐渭在出狱之后游历了许多地方，到了汉蒙边界的宣府，感受了不同于江南的自然风光和人文文化，重新变得洒脱。本文还将诗人对严氏女与三娘子两位女性的态度进行了对比研究，认为徐渭对女性大多数时候都很宽容、怜惜，并不吝啬溢美之词。最后是结论，笔者总结了绪论提到的几个需要深度发掘的要点，并说明了本文仍有问题值得进一步研究。The introduction of this thesis opens by stating clearly that the range of study is on Xu Wei’s Frontier Poems. The Frontier Poems include both the Sea Frontier Poems and the Land Frontier Poems. The meanings of different types of Frontier Poems are defined. Next, I distinguish that among more than two thousand poems, which are the frontier ones. Lastly, several points of interest are raised. Main body of this thesis includes three chapters which are the most important parts. They are arranged according to the time at which the poet wrote those poems analyzed. Chapter 1 is the close reading of poems written while the poet was fighting the Japanese invaders. The selected poems are “A Tribute to General Yu”, “Nine Poems Propagating the Victory on Mountain Kan”, “The Daughter of Mr. Yan”. His Frontier Poems not only describe the battlefield and propagate the victory, but also reflect the meaning of war and show the poet’s desire of success. In addition, “The Daughter of Mr. Yan” is a masterpiece of Xu Wei’s Frontier Poems and it is talking about a female character. It has great value for studying. Chapter 2 is the close reading of poems written while the poet was working as a secretary under General Hu. The selected poems are “General Hu Visits the Zhe Province”, “Paying Tribute to General Qi by Presenting a Poem”. Unlike the previous period, Xu Wei no longer fighted as a soldier; he worked as a secretary and sometimes offers his stratagem to his boss, General Hu. General Hu had close relationship with the notorious government official, Yan Song. The poet hated Yan Song very much but had to serve him well. He knew well about what he should do and should not to do in order to promote faster. Therefore, even though he felt very uncomfortable serving Yan Song, he made his mind to stand it. I also chose, Shen Mingchen, another poet’s frontier poem to compare with “Paying Tribute to General Qi by Presenting a Poem”. Chapter 3 is the close reading of poems written while the poet was working as a secretary under General Wu. The selected poems are “Bilateral Market”, “Three Poems Written at the north-western border”. The poet wrote many poems to describe the harmonious scene in the north-western area. Before he became Wu’s secretary, he had gone through a lot of trauma and got very depressed. However, after he had witnessed that the Han people and the Meng people could live near to each other harmoniously, he was deeply impressed and started to walk out of the depression. In his poems, he praised a female of Meng race for her openness and brightness. I compared the poet’s attitude towards the daughter of Mr. Yan and the Meng female. Lastly, there is the conclusion. I summarize the points of interests mentioned in introduction and then point out the parts that need further study. Key Words: Xu Wei, Frontier Poems, Sea Frontier Poems, Land Frontier Poems.